2010
DOI: 10.1056/nejmoa1002926
|View full text |Cite
|
Sign up to set email alerts
|

Exome Sequencing,ANGPTL3Mutations, and Familial Combined Hypolipidemia

Abstract: SUMMARY We sequenced all protein-coding regions of the genome (the “exome”) in two family members with combined hypolipidemia, marked by extremely low plasma levels of low-density lipoprotein (LDL) cholesterol, high-density lipoprotein (HDL) cholesterol, and triglycerides. These two participants were compound heterozygotes for two distinct nonsense mutations in ANGPTL3 (encoding the angiopoietin-like 3 protein). ANGPTL3 has been reported to inhibit lipoprotein lipase and endothelial lipase, thereby increasing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
468
3
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 649 publications
(496 citation statements)
references
References 22 publications
11
468
3
3
Order By: Relevance
“…The family members share a common architecture, comprising an extended N-terminal domain and a C-terminal fibrinogen-like domain. Genetic studies have revealed that two closely related family members, ANGPTL3 and ANGPTL4, play pivotal roles in the trafficking and metabolism of lipids and lipoproteins (4)(5)(6)(7). Mutations that disrupt ANGPTL3 are associated with greatly reduced plasma levels of triacylglycerol (TAG) and cholesterol in mice (5) and in humans (4).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The family members share a common architecture, comprising an extended N-terminal domain and a C-terminal fibrinogen-like domain. Genetic studies have revealed that two closely related family members, ANGPTL3 and ANGPTL4, play pivotal roles in the trafficking and metabolism of lipids and lipoproteins (4)(5)(6)(7). Mutations that disrupt ANGPTL3 are associated with greatly reduced plasma levels of triacylglycerol (TAG) and cholesterol in mice (5) and in humans (4).…”
mentioning
confidence: 99%
“…Genetic studies have revealed that two closely related family members, ANGPTL3 and ANGPTL4, play pivotal roles in the trafficking and metabolism of lipids and lipoproteins (4)(5)(6)(7). Mutations that disrupt ANGPTL3 are associated with greatly reduced plasma levels of triacylglycerol (TAG) and cholesterol in mice (5) and in humans (4). Mice lacking ANGPTL4 also have markedly reduced levels of plasma TAG and cholesterol (8,9), and sequence variations in ANGPTL4 are associated with lower plasma TAG levels in humans (7).…”
mentioning
confidence: 99%
“…These observations from mice suggested that complete lack of ANGPTL3 should lead to lower levels of TRLs and LDLs. In support of this idea, a family has been identified 13 whose members have exceptionally low levels of TRLs and LDLs in their blood as a result of the complete absence of ANGPTL3.…”
Section: S E K a R K At H I R E S A Nmentioning
confidence: 95%
“…Un tout récent article du New England Journal of Medicine [6] montre comment cette approche peut élucider un déterminant génétique d'une affection complexe. Il s'agit dans ce cas de l'hypolipidémie familiale, qui se manifeste par un taux de cholestérol LDL (low-density lipoprotein) très bas entraînant différentes manifestations cliniques (stéatose hépatique, malabsorption des lipides, etc.).…”
Section: L'hypolipidémie Ou L'exploitation Intelligente D'un Cas Limiteunclassified
“…Une étude a alors été effectuée sur l'ensemble de la famille, qui comporte trois générations, avec, chez de nombreux individus, des anomalies plus ou moins marquées au niveau des LDL. [6]. Le statut de chaque personne du point de vue du gène ANGPTL3 a été déterminé pour 3 générations (I, II et III).…”
Section: Dix-huit Mille Variants -Et Un Gène Identifié !unclassified